Third International IEEE Workshop on Software Evolvability 2007 2007
DOI: 10.1109/software-evolvability.2007.14
|View full text |Cite
|
Sign up to set email alerts
|

The Darwin Project: Evolvability of Software-Intensive Systems

Abstract: This paper presents the Darwin 1 project. This applied research project is currently conducted at Philips Medical Systems and focuses on the evolvability of software-intensive systems, with as use case Magnetic Resonance Imaging (MRI) systems. We not only discuss evolvability of software-intensive systems in general, but also describe the project and its research areas.Third IEEE Workshop on Software Evolvability 0-7695-3002-8/07 $25.00 The first research topic in this area concentrates on the communication in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…This is both a finding of the research community [14], and our own observation as part of our research on evolvability of softwareintensive systems [23]. On the one hand, it is hard and expensive to obtain and integrate execution traces from heterogeneous systems.…”
Section: Introductionmentioning
confidence: 92%
“…This is both a finding of the research community [14], and our own observation as part of our research on evolvability of softwareintensive systems [23]. On the one hand, it is hard and expensive to obtain and integrate execution traces from heterogeneous systems.…”
Section: Introductionmentioning
confidence: 92%
“…Second, the cost of training or preparation to use the approach can be neglected. This was possible because the approach was developed and validated in close collaboration between researchers and Philips Healthcare MRI practitioners as part of the Darwin project [3], an industry-as-laboratory research project. Finally, we designed a top-down strategy and assembled a team.…”
Section: Case Study Concerns and Decisionsmentioning
confidence: 99%
“…If system documentation is available, it may go into too much technical detail to offer relevant and accurate architectural information. As part of our research project on evolvability of software-intensive systems [3], we have observed that these situations are common in practice and development organizations constantly need up-to-date and accessible architectural information to steer the ✩ This work has been carried out as a part of the Darwin project at Philips Healthcare under the responsibilities of the Embedded Systems Institute. This project is partially supported by the Dutch Ministry of Economic Affairs under the BSIK program.…”
Section: Introductionmentioning
confidence: 99%